The Burgess boys : a novel - Strout, Elizabeth (New York : Random House, 2013)
Catalyzed by a nephew's thoughtless prank, a pair of brothers confront painful psychological issues surrounding the freak accident that killed their father when they were boys, a loss linked to a heartbreaking deception that shaped their personal and professional lives.
Maine author. Elizabeth Strout lives in Maine and New York City.
Keywords: Brothers -- Fiction; Domestic fiction; Psychological fiction; Maine -- Fiction